An Overview of the Level of Knowledge of Medical Student of Universitas Sumatera Utara about Risky Pregnancies - Kindry Manik; Hotma Partogi Pasaribu (Sumatera Medical Journal, 2022)
Background. One indicator of a country's health status is the Maternal Mortality Rate (MMR). Every pregnant woman has potential dangers during pregnancy, childbirth, and puerperium. Until now, in all parts of the world, risky pregnancies, especially high-risk pregnancies, are still a problem in health services, especially in developing countries. In Indonesia, MMR decreased during the period 1991-2015 from 390 to 305 per 100,000 live births. However, this is still far from the MDGs target goal, which is 102 per 100,000 live births. Many women are still pregnant or giving birth at a risky age. This condition leads to many complications (especially high-risk pregnancies) such as miscarriage, premature birth, genetic disorders, and even death. This may occur due to the lack of knowledge and education of general practitioners who serve pregnant women, especially in peripheral areas. Objective. This study aims to determine the knowledge level of Medical students of Universitas Sumatera Utara about risky pregnancy. Methods. This research was conducted in a quantitative descriptive study with a cross-sectional design. This research was conducted at the Faculty of Medicine, Universitas Sumatera Utara. The samples of this study were students of the Faculty of Medicine, Universitas Sumatera Utara, which were taken by proportionate stratified. Primary data was collected using a questionnaire containing 21 true and false questions. Result. It was found that the knowledge of students from the Faculty of Medicine, Universitas Sumatera Utara class 2018 and 2019 regarding risky pregnancies was good (85.7%). Conclusion. Students of the Faculty of Medicine, Universitas Sumatera Utara, class of 2019 have better knowledge than students of class 2018.